Challenges of IoT Based New Generation Smart-Government (Journal of Informatics and Mathematical Sciences, 2018)
A milestone of Information Technology in 21st century is Internet of Things (IoT). The most significant aspect of IoT is its application in smart cities. The IoT is considered as software foundation of modern smart cities and is making revolution in the development of smart-government. The IoT is the backbone of smart cities and smart cities are the backbone of a smart-government. There are two types of smart-governments: (1) New Generation Smart-Government, (2) Extended Smart-Government. We illustrate the differences between the new generation smart-government and the extended smart-government. In this paper, a framework of new generation smart-government is proposed with inner and outer layer process. This framework is designed to illustrate the players, process and the challenges of the smart-government. Are search survey is carried out to study the challenges of smart-government from the perspectives of India, USA and Kuwait. It is observed that the challenges differ from country to country. The survey reports bring out some interesting facts that mindscaping is the biggest challenge for Kuwait, investment is the biggest challenge for India and security & privacy is the biggest challenge for USA.
Keywords: Internet of things; Internet of everything; Smart cities; Traditional e-Government; Government 2.0; Smart-government